Customer Perception on Instagram Marketing of Tourism Services: A Study of Delhi NCR - Das, Manoj; Singh, Karnail (RESEARCH HUB International Multidisciplinary Research Journal, 2026)
The rapid growth of social media has significantly transformed the way travelers discover destinations and plan their trips. Among various platforms, Instagram has emerged as a powerful tool influencing tourism marketing through visual storytelling, influencer content, and user-generated experiences. This study examines the impact of Instagram marketing factors on destination selection and the promotion of tourism services among travelers in the Delhi NCR region. A quantitative research design was adopted, and data were collected from 250 Instagram users through a structured questionnaire using a five-point Likert scale. The study analyzed key variables including visual appeal, user-generated content, influencer engagement, brand endorsements, trust in influencers, and trust in travel companies. The results of multiple regression analysis indicate that visual appeal, user-generated content, and influencer engagement significantly influence destination selection, with influencer engagement emerging as the strongest predictor. However, brand endorsements were not found to have a significant impact on destination choice. Furthermore, trust in Instagram influencers and trust in travel companies were found to significantly influence the promotion of tourism services, with influencer trust showing a stronger effect. The findings highlight that authenticity, engaging content, and credibility play a crucial role in shaping travelers’ perceptions and decisions. The study contributes to the growing literature on social media marketing in tourism and provides practical insights for tourism businesses in Delhi NCR to design more effective Instagram marketing strategies.